Prevalence and clinical correlates of Gardnerella spp., Fannyhessea vaginae, Lactobacillus crispatus and L. iners in pregnant women in Bukavu, Democratic Republic of the Congo - Lisa Himschoot; Guy Mulinganya; Guy Mulinganya; Guy Mulinganya; Tess Rogier; Ghislain Bisimwa; Ghislain Bisimwa; Freddy Kampara; Freddy Kampara; Yvette Kujirakwinja; Yvette Kujirakwinja; Jules Mongane; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundGardnerella is a key pathogen in bacterial vaginosis (BV), but the role of the different Gardnerella species remains unclear. We investigated the role of four Gardnerella species, as well as Fannyhessea vaginae, Lactobacillus crispatus and L. iners in BV.MethodsFrom 331 pregnant women from the Democratic Republic of the Congo, BV was diagnosed using Nugent scoring and a cervicovaginal lavage was used to quantify G. leopoldii, G. piotii, G. swidsinskii, G. vaginalis, F. vaginae, L. crispatus and L. iners by qPCR. Univariate associations between these species and clinical outcomes were assessed. A logistic regression model and ROC curves were calculated to determine the best diagnostic marker for BV.ResultsHere, L. iners (75.8%) was the most prevalent species and G. vaginalis (36.0%) the most common Gardnerella species. All investigated Gardnerella spp. were prevalent (50.9-57.9%) in women with (asymptomatic) BV. Univariate analysis revealed no significant associations with clinical symptoms of BV, while F. vaginae (positive Whiff test, high pH), G. vaginalis (high pH) and L. crispatus (low pH) were associated with signs of BV. G. piotii was associated with markers of urinary tract infection. Women with L. iners had higher odds of delivering preterm. ROC analyses showed that F. vaginae was the best marker for BV (AUC 0.81), and the combined model further increased the diagnostic performance (AUC 0.90).ConclusionAll Gardnerella species were involved in BV, although none were associated with the most important clinical symptoms of BV and none emerged as a superior molecular marker for BV.